Electronic ferroelectricity in monolayer graphene moiré superlattices - Le Zhang; Jing Ding; Hanxiao Xiang; Naitian Liu; Wenqiang Zhou; Linfeng Wu; Na Xin; Kenji Watanabe; Takashi Taniguchi; Shuigang Xu (Nature Communications)
Abstract Extending ferroelectric materials to two-dimensional limit provides versatile applications for the development of next-generation nonvolatile devices. Conventional ferroelectricity requires materials consisting of at least two constituent elements associated with polar crystalline structures. Monolayer graphene as an elementary two-dimensional material unlikely exhibits ferroelectric order due to its highly centrosymmetric hexagonal lattices. Here, we report the observations of electronic ferroelectricity in monolayer graphene by introducing asymmetric moiré superlattice at the graphene/h-BN interface, in which the electric polarization stems from electron-hole dipoles. The polarization switching is probed through the measurements of itinerant Hall carrier density up to room temperature, manifesting as standard polarization-electric field hysteresis loops. We find ferroelectricity in graphene moiré systems exhibits generally similar characteristics in monolayer, bilayer, and trilayer graphene, which indicates layer polarization is not essential to observe the ferroelectricity. Furthermore, we demonstrate the applications of this ferroelectric moiré structures in multi-state nonvolatile data storage with high retention and the emulation of versatile synaptic behaviors. Our work not only provides insights into the fundamental understanding of ferroelectricity, but also demonstrates the potential of graphene for high-speed and multi-state nonvolatile memory applications.